Clinical Characteristics of Cytomegalovirus Disease of the Upper Gastrointestinal Tract: A 10-Year Multicenter Retrospective Study - Ga-Ram You; Seon-Young Park; Hye-Su You; Seung-Young Seo; Sung-Kyun Yim; Byung-Chul Jin; Jung-In Lee; Young-Dae Kim; Suck-Chei Choi; Chan-Guk Park; Wan-Sik Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2023)
Objectives Gastrointestinal cytomegalovirus (CMV) disease is a major contributor to mortality in immunocompromised patients. Few studies have discussed upper gastrointestinal CMV (UGICMV) disease in immunocompetent patients. We compared the clinical outcomes of UGI-CMV between immunocompromised and immunocompetent patients. Methods This retrospective study included patients with UGI-CMV disease from five tertiary hospitals across Korea (2010– 2022). Patients’ clinical data and outcomes were recorded. Results UGI-CMV was diagnosed in 54 patients; 27 (50.0%) had esophageal, 24 (44.4%) had gastric, and 3 patients (5.6%) had duodenal involvement. Patients’ median age was 64 years (interquartile range 53–75 years), and the most common comorbidities included hypertension (57.4%) and diabetes (38.9%). The predominant symptom was abdominal pain (46.3%), and the most common endoscopic finding was ulcers (70.4%). Antiviral treatment was administered to 31 patients, and 23 patients underwent observation without treatment. We investigated 32 immunocompromised (59.3%) and 22 immunocompetent (40.7%) patients and observed no intergroup differences in comorbidities and in laboratory and endoscopic findings. Immunocompromised patients had longer length of hospitalization (median 46.2 days vs. 20.0 days, p=0.001). However, treatment outcomes, including the need for intensive care unit admission and mortality did not significantly differ. The overall mortality rate was 13.0%; one patient from the immunocompromised group died of UGI-CMV disease. The treatment success rate was higher in immunocompromised patients who received antiviral therapy (p=0.011). Conclusions UGI-CMV disease is not uncommon in immunocompetent patients, although symptoms are milder than those in immunocompromised patients. Our findings emphasize the importance of clinical vigilance for accurate diagnosis of CMV infection, particularly in susceptible symptomatic patients and highlight the need for active antiviral treatment for management of immunocompromised patients.